Impact of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight for the Identification of Gram-Positive Bloodstream Pathogens without Antimicrobial Stewardship Intervention in Hospitalized Children - Herrera, Lisa; Culbreath, Karissa; Dehority, Walter (Journal of Pediatric Infectious Diseases, 2019)
We performed a 2-year retrospective cohort study of inpatient children with growth of gram-positive bacteria from blood cultures identified with and without the use of matrix-assisted laser-desorption/ionization time-of-flight (MALDI-TOF) in the absence of an antimicrobial stewardship program. Use of MALDI-TOF reduced the time to organism identification by 15.7 hours (p < 0.0001). However, no differences in length of stay, time to optimization of antimicrobial therapy, or time to discontinuation of antibiotics for growth of contaminants were documented, suggesting that such potential patient-oriented benefits of MALDI-TOF may only be evident in the presence of a concurrent antimicrobial stewardship program.
Keywords: MALDI-TOF; bacteremia; antimicrobial stewardship